Survival in patients with breast cancer in the republic of dagestan - O. M. Magomedov (Опухоли женской репродуктивной системы, 2014)
By taking into account the mortality/morbidity ratio, overall survival rates in patients with breast cancer were calculated in the Republic of Dagestan (RD) as a whole and its regions. The survival in the RG was ascertained to vary with the residence of women. High and low survival towns, districts, and administrative centers where the survival rates had a negative meaning (i.e. mortality rates exceed morbidity ones) were found. It is concluded that the situation established in the RD has resulted from failure in the organiza- tion of cancer service.